2006
DOI: 10.1155/2007/628987
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Color Reactions for Spectrophotometric Determination of Pitavastatin Calcium in Bulk Drugs and in Pharmaceutical Formulations

Abstract: Three simple, sensitive and cost effective Spectrophotometric methods are described for the determination of pitavastatin calcium (PST) in bulk drugs and in pharmaceutical formulations. These methods are based on the oxidation of PST by ferric chloride in presence of o-phenanthroline (Method A) or 2, 2' bipyridyl (Method B) or potassium ferricyanide (Method C). The colored complex formed was measured at 510, 530 and 755 nm for method A, B and C respectively against the reagent blank prepared in the same manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…A mean recovery of 99.01% for Pitava and 97.72% for Flovas was achieved by the present work. The detailed results of the pharmaceutical analysis compared with some other reported analytical methods [26] , [27] are presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mean recovery of 99.01% for Pitava and 97.72% for Flovas was achieved by the present work. The detailed results of the pharmaceutical analysis compared with some other reported analytical methods [26] , [27] are presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Pitavastatin (PST), 7-[2-Cyclopropyl-4-(4-fluoro-phenyl)-quinolin-3-yl]-3,5-dihydroxy-hept-6-enoic acid, is an anti-hyperlipidemic drug that works by inhibiting conversion of HMG-CoA to mevalonic acid in hepatocytes, through competitive blockade of HMG-CoA reductase, the rate-limiting enzyme in cholesterol biosynthesis [23] , [24] . The quantification of pitavastatin has been reported by many analytical techniques [25] , [26] , [27] , [28] , [29] ; however, these methods are either costlier or time consuming. The present study was focused on developing a simple, economical and highly sensitive method for the quantification of pitavastatin in pharmaceutical formulations and biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…Like all other statins, pitavastatin calcium is used for controlling hypercholesterolemia and for the prevention of cardiovascular disease. The literature review exposed several analytical methods for the determination of pitavastatin calcium by titrimetric 2 , visible spectroscopic methods [3][4][5][6] , stability indicating studies [7][8][9] , fluorimetric method 10 , chromatographic methods like HPTLC 11 , RP-LC [12][13] , HPLC 14 , HPTLC 15 and LC-MS/MS [16][17] , Electro analytical techniques. [18][19] The above reported methods suffered from various disadvantages like heating step, slow reaction, extraction step, multi step reactions, tedious control of experimental variables and less sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] PTV was approved by USFDA in 2009. A literature survey revealed that pitavastatin can be estimated by spectrophotometry, [8] high-performance thin-layer chromatography (HPTLC), [9,10] and liquid chromatography (LC) [11][12][13] in bulk and pharmaceutical formulation. The LC=MS=MS method has been reported for the estimation of pitavastatin in human plasma.…”
Section: Introductionmentioning
confidence: 99%